Monitoring neonatal abstinence syndrome in buprenorphine-exposed in vitro fertilization twins: A case study. Issue 4 (1st October 2016) - Brandt, Laura; Swoboda, Patrick; Fischer, Gabriele; Unger, Annemarie
ABSTRACT: Background: Prior studies have reported on the pregnancies and outcomes of in vitro fertilization (IVF) in special subpopulations; however, there is a lack of studies on opioid-exposed IVF-conceived neonates. Case Presentation: A young adult IVF-pregnant woman was maintained on buprenorphine throughout pregnancy and received follow-up from the addiction clinic from estimated gestational week 32. She delivered healthy dichorionic twins via cesarean section at 38 weeks gestational age (buprenorphine dose at time of delivery: 16 mg). All maternal supervised urinalysis taken as of gestational week 32 were negative for concomitant substances (prior to treatment initiation at the addiction clinic, only self-reports of abstinence from concomitant substances were available). Both healthy children (male birth weight: 3140 g, female birth weight: 2650 g) developed an unusual course of neonatal abstinence syndrome (NAS) requiring extensive treatment (total morphine dose male: 22 mg, and female: 26.75 mg; length of treatment: 33 and 34 days, respectively; duration of hospitalization: 40 days). Discussion: The highly severe and long-lasting NAS in both neonates represents a very unusual course following an uneventful pregnancy, and influencing iatrogenic factors cannot be ruled out. Given the multiple variables influencing infant outcomes, this highlights the importance of high-quality, evidence-based standard operating procedures, which (1) are initiated as early as possible during pregnancy to minimize risk factors for adverse infant outcomes, such as concomitant substance use during pregnancy; (2) support the substance-dependent woman throughout the postpartum period, especially in cases of multiple and/or IVF-conceived pregnancies, where additional challenges may arise; and (3) consider the right of everyone to the enjoyment of the highest attainable standard of physical and mental health.